Probing the mechanism of the interaction between l‐cysteine‐capped‐CdTe quantum dots and Hg2+ using capillary electrophoresis with ensemble techniques. Issue 6 (27th February 2015) - Xu, Laifang; Hao, Junjie; Yi, Tao; Xu, Yinyin; Niu, Xiaoying; Ren, Cuiling; Chen, Hongli; Chen, Xingguo
<x xml:space="preserve">Abstract</x> A good understanding of the mechanism of interaction between quantum dots (QDs) and heavy metal ions is essential for the design of more effective sensor systems. In this work, CE was introduced to explore how l‐cysteine‐capped‐CdTe QDs (l‐cys‐CdTe QDs) interacts with Hg2+. The change in electrophoretic mobility can synchronously reflect the change in the composition and property of QDs. The effects of the free and capping ligands on the system are discussed in detail. ESI‐MS, dynamic light scattering (DLS), zeta potential, and fluorescence (FL) were also applied as cooperative tools to study the interaction mechanism. Furthermore, the interaction mechanism, which principally depended on the concentration of Hg2+, was proposed reasonably. At the low concentration of Hg2+, the formation of a static complex between Hg2+ and the carboxyl and amino groups of l‐cys‐CdTe QDs surface was responsible for the FL quenching. With the increase of Hg2+ concentration, the capping l‐cys was stripped from the surface of l‐cys‐CdTe QDs due to the high affinity of Hg2+ to the thiol group of l‐cys. Our study demonstrates that CE can reveal the mechanism of the interaction between QDs and heavy metal ions, such as FL quenching.